Progress on spinal cord stimulation in treatment of peripheral neuropathy - ZONG Yun⁃fei; DONG Tie⁃yan; BAO Min (Chinese Journal of Contemporary Neurology and Neurosurgery)
Spinal cord stimulation (SCS) is a minimally invasive neuromodulation technique that has been widely applied and recognized for its efficacy in peripheral neuropathy such as diabetic peripheral neuropathy (DPN), trigeminal neuralgia (TN), trigeminal postherpetic neuralgia, chemotherapy⁃induced peripheral neuropathy (CIPN), chronic groin pain, and lumbosacral radiculopathy syndrome. This article reviews the basic principles of SCS and its latest applications in peripheral neuropathy to promote its clinical application in peripheral neuropathy.